LEGAL ANALYSIS OF DUAL CITIZENSHIP RULE IN INDONESIA - Najwa Maulida Sabrina; Grace Natalie Lim (Jurnal Meta-Yuridis, 2023)
Globalization has transformed the perception of national borders as barriers to human interaction, resulting in an increase in mixed marriages. Issues often arise, particularly concerning the citizenship status of a spouse married to a foreigner and their children resulting from such mixed marriages. The method employed in this study is normative juridical, thereby analyzing legal issues within the framework of applicable laws and legal theories. The findings of this research reveal that mixed marriages frequently face disputes regarding the citizenship status of children, as exemplified by the case under study, which involves the marriage between Marcellina, an Indonesian citizen from Surabaya, and John, a citizen of the United States. Meanwhile, according to the prevailing national law, children from mixed marriages will hold dual citizenship until the age of 18 or upon marriage. This research emphasizes the importance of understanding the relevant legal provisions and complying with the procedures established by the Indonesian government concerning mixed marriages. The objective is to maintain clarity and the validity of the citizenship status of both the spouses and the children involved in mixed marriages.